The Superiority of T2*MRI Over Serum Ferritin in the Evaluation of Secondary Iron Overload in a Chronic Kidney Disease Patient: A Case Report - Al-Mashdali A; Alyafei T; Yassin M (Journal of Blood Medicine, 2021)
Abdulrahman Al-Mashdali,1 Tahiya Alyafei,2 Mohamed Yassin3 1Department of Internal Medicine, Hamad Medical Corporation, Doha, Qatar; 2Department of Clinical Imaging, Hamad Medical Corporation, Doha, Qatar; 3National Center for Cancer Care and Research, Department of Oncology, Hematology and BMT Section, Hamad Medical Corporation, Doha, QatarCorrespondence: Abdulrahman Al-MashdaliDepartment of Internal Medicine, Hamad Medical Corporation (HMC), P.O. Box 3050, Al Rayyan Road, Doha, QatarTel +967 507 008 16Email AAlmashdali@hamad.qaAbstract: Secondary iron overload is increasingly encountered in chronic kidney disease (CKD) patients because of the frequent use of parenteral iron products, especially in hemodialysis patients. Serum ferritin has been commonly used to monitor iron overload in these patients; however, other conditions can be associated with the high serum ferritin, like infections and inflammatory conditions. Currently, T2*MRI of the heart and liver is the preferred investigation for evaluating liver iron concentration (LIC) and cardiac iron concentration, which reflect the state of iron overload. Few studies observe a positive correlation between serum iron and LIC in CKD patients and postulate that serum ferritin exceeding 290 mcg/L should indicate significant iron overload and necessitates further MRI evaluation. However, here, we present a patient with a history of ESRD for which she underwent renal transplantation twice referred to our clinic due to persistent elevation in serum ferritin level (> 1000 mcg/L) for several years. T2*MRI of the heart and liver revealed the absence of iron overload. Our objective of this case is to demonstrate the accuracy of T2*MRI over serum ferritin in evaluating iron overload and questioning the positive correlation between serum ferritin and LIC in CKD patients.Keywords: secondary iron overload, chronic kidney disease, serum ferritin, T2*MRI, liver iron concentration